Analisis Dimensi Street Inlet pada Ruas Jalan Simpang Gajayana Kota Malang - Agustian, Dominikus; Pandulu, Galih Damar; Sulistyani, Kiki Frida (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
The increased development in Malang has a significant impact on changes in land use. The large number of new buildings results in a reduction in the absorption area which prevents rainwater from seeping into the ground, resulting in inundation. In the Malang Simpang Gajayana Road section, inundation often occurs due to lack of access to water to enter the channel and reduced drainage capacity. To overcome this problem, Street Inlet planning is needed as water access to enter the drainage channel. The purpose of this study is to obtain an effective inlet dimension. In this study the first data collection was carried out in the form of primary and secondary data, then data analysis was carried out such as hydrological analysis, hydraulics and Inlet dimensions. From the results of the analysis and calculations, it is found that the planned inlet dimensions on the left and right of the road are 37x31 cm with a grid size of 3 x 21 cm with 4 holes. Based on the results of the analysis of the Street Inlet condition of the plan, the distance between the Inlet and the type of Inlet is uniformed with the aim of reducing the inundation that occurs and can facilitate water entry into the Inlet in accordance with road topographic conditions. After designing this Street Inlet, the water conditions on the road surface that initially run off can be maximized into the drainage channel with the planned number and distance.